Freestanding Needle Flower Structure CuCo2S4 on Carbon Cloth for Flexible High Energy Supercapacitors With the Gel Electrolyte - Xie, Tian; Xu, Jinxiao; Wang, Jie; Ma, Chuanli; Su, Linghao; Dong, Fengying; Gong, Liangyu (Frontiers in Chemistry, 2020)
A facile hydrothermal approach was adopted to the direct synthesis of bimetallic sulfide (CuCo2S4) on carbon cloth (CC) without binders for the supercapacitor's electrodes. A possible formation mechanism was proposed. The prepared bimetallic electrode exhibited a high specific capacitance (Csp) of 1,312 F·g−1 at 1 A·g−1, and an excellent capacitance retention of 94% at 5 A·g−1 over 5,000 cycles. In addition, the asymmetric supercapacitor (CuCo2S4/CC//AC/CC) exhibited energy density (42.9 wh·kg−1 at 0.8 kW·kg−1) and outstanding cycle performance (80% initial capacity retention after 5,000 cycles at 10 A·g−1). It should be noted that the electrochemical performance of a supercapacitor device is quite stable at different bending angles. Two charged devices in series can light 28 red-colored LEDs (2.0 V) for 5 min. All of this serves to indicate the potentially high application value of CuCo2S4.